Image, Perceived Quality, Perceived Value and Student Loyalty in the Higher Education Institutions - Usman, Umar; Mohd Mokhtar, Sany Sanuri (2017)
Today, the fast growing trade in the global business is in the higher education institutions (HEIs) business follows closely the trend of other service sectors.HEIs in Nigeria are facing the problems of low academic staff to student ratio, university image and reputation published by the HEIs world university rankings, in which HEIs in Nigeria are ranked low in terms of teaching, research and international outlook.The objectives are developed to; examine the relationship between Image, Perceived Quality, Perceived Value and Student Loyalty in the Higher Education Institutions.The primary data was used; the students of the public universities in Nigeria are the population used in this research (unit of analysis) is public university students.In a similar way, the study uses the cross-sectional research design in which data was collected throughout the entire period of the study. The units of analysis of the present study are the federal universities students in Nigeria, Similarly, the PLS-SEM approach was used to analyze the data collected. The results show a significant relationship between the independent variables and dependent variable which is student loyalty.